1999
DOI: 10.1002/(sici)1521-3927(19991101)20:11<602::aid-marc602>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins in polymer chemistry: Influence of methylated β-cyclodextrin as host on the free radical copolymerization reactivity ratios of isobornyl acrylate and butyl acrylate as guest monomers in aqueous medium

Abstract: SUMMARY: Methylated b-cyclodextrin (me-b-CD) was used to complex the hydrophobic monomers isobornyl acrylate (1) and butyl acrylate (2) yielding the water-soluble host/guest complexes isobornyl acrylate/me-b-CD (1a) and butyl acrylate/me-b-CD (2a). The included monomers were copolymerized in water by free-radical mechanism and the kinetics were studied. In order to evaluate these results, the corresponding uncomplexed monomers 1 and 2 were also copolymerized in organic solution. The reactivity ratios of 1a and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 4 publications
(6 reference statements)
0
25
0
Order By: Relevance
“…[4,5] In the case of dodecanethiol however the 1 H NMR-signals are overlayed by cyclodextrin resonances. The spot of the complex shows the same UV activity as the pure dodecanethiol and in addition it reacts with iodine in the same way as me-b-CD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4,5] In the case of dodecanethiol however the 1 H NMR-signals are overlayed by cyclodextrin resonances. The spot of the complex shows the same UV activity as the pure dodecanethiol and in addition it reacts with iodine in the same way as me-b-CD.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Also, some patents describe the use of CDs, preferably in catalytic amounts, in order to improve, for example, emulsion polymerizations. [1][2][3][4][5][6] We also described that the reactivity ratios of the copolymerization of isobornyl acrylate/CD and butyl acrylate/CD complexes differ significantly from the r-values of the uncomplexed monomers in organic medium. We found that during the free-radical homopolymerization and copolymerization of the complexed monomers, the CD slips off from the monomer during chain propagation, and the polymer precipitates, while the CD remains in the aqueous phase due to its high water solubility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the preparation and polymerization of equimolar cyclodextrin complexes of commercial standard monomers like styrene 1 and methyl methacrylate (MMA have been described. It was also shown that the precipitation polymerization of a cyclodextrin complex of a poorly water-soluble monomer like MMA can be described by kinetic equations similar to those for the classical polymerization in solution [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, examples whereby CDs hinder the polymerization are known 33. Furthermore, the influence of CD on the copolymerization parameters of hydrophobic monomers was examined 34,35. In some examples, it was also shown that the copolymerization of CD‐complexed hydrophobic monomers together with hydrophilic monomers in water could only be performed in good yields by the use of CDs 36,37…”
Section: Introductionmentioning
confidence: 99%